Elastic moduli and hardness of η-Ta2N3 from nanoindentation measurements. (30th July 2015) - Bourguille, Judith; Brinza, Ovidiu; Tétard, Florent; Nikitin, Sergey; Zerr, Andreas
Abstract: Nanoindentation testing was used to determine elastic moduli and hardness of η -Ta2 N3, a novel stiff and hard high-pressure compound recoverable at ambient conditions. For a sample having porosity of 14% we confirmed densification of its upper layer induced by mechanical polishing: At depths we obtained higher reduced elastic modulus and higher hardness when compared with the sample without the densified layer. Using the experimental values of and of porosity we derived the shear modulus of dense η -Ta2 N3 to be . Hardness of the porous η -Ta2 N3 was measured to be 18 GPa and its fracture toughness estimated to exceed . The Pugh criterion suggests a high malleability of η -Ta2 N3 which could explain the observed surface densification.